2015
DOI: 10.2166/wst.2015.520
|View full text |Cite
|
Sign up to set email alerts
|

Biogas production in an anaerobic sequencing batch reactor by using tequila vinasses: effect of pH and temperature

Abstract: In recent years, anaerobic digestion has been recognized as a suitable alternative for tequila vinasses treatment due to its high energy recovery and chemical oxygen demand (COD) removal efficiency. However, key factors such as the lack of suitable monitoring schemes and the presence of load disturbances, which may induce unstable operating conditions in continuous systems, have limited its application at full scale. Therefore, the aim of this work was to evaluate the anaerobic sequencing batch reactor (AnSBR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…The PBR was fed with tequila vinasses stored in three 5000 L tanks at room temperature. The initial COD of tequila vinasses was 50 g L ‐1 but decreased gradually during storage due to natural fermentation of organic compounds, agreeing with previous studies . The natural fermentation observed during vinasses storage and the variability of organic compounds that were fed to the PBR simulates the changes in substrate composition to which full‐scale reactors are subjected, since the vinasses are commonly cooled and stored in large ponds.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The PBR was fed with tequila vinasses stored in three 5000 L tanks at room temperature. The initial COD of tequila vinasses was 50 g L ‐1 but decreased gradually during storage due to natural fermentation of organic compounds, agreeing with previous studies . The natural fermentation observed during vinasses storage and the variability of organic compounds that were fed to the PBR simulates the changes in substrate composition to which full‐scale reactors are subjected, since the vinasses are commonly cooled and stored in large ponds.…”
Section: Resultssupporting
confidence: 88%
“…This factor correlates the partial and intermediate alkalinities that are related to bicarbonate and VFAs buffer capacities and has been suggested as a parameter to evaluate the stability of anaerobic digestion processes . Even though it has been reported that successful anaerobic digestion occurs at α values below 0.3, it is clear that during the present study, the stability of the process was maintained at slightly higher values. The probable reason for this difference may be related to the titration processes, since unlike previous work where titration was performed manually, during the present work it was performed by an automated device (AnaSense ® ).…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations